Теоретичні положення розвитку цифрових фінансових інструментів управління приватним капіталом - Манойленко, Олександр Володимирович; Кайдалов, Ігор Володимирович (Університет економіки і підприємництва, 2025)
Стрімка цифровізація фінансового сектора значно змінила та продовжує далі змінювати способи формування приватного капіталу, додаючи нові інструменти та вимагаючи утворення цілісної екосистеми їх застосування. Відповідно виникла науково-прикладна проблема подолання фрагментарності сучасних цифрових інструментів управління приватним капіталом, розв’язання якої визначає мету дослідження як обґрунтування теоретичних положень щодо розвитку цифрового управління приватним капіталом. Досягнення поставленої мети базується на системному аналізі, концептуальному моделюванні та методології предметно-орієнтованого проектування (Domain-Driven Design, DDD). Концептуалізація предметної області здійснена через розробку холістичної моделі цифрового управління приватним капіталом, яка базується на синтезі поведінкових, ціннісних та заснованих на розподіленому технологічному реєстрі інструментів.

The rapid digitalization of the fiancial sector has fundamentally transformed, and continues to transform, the way private capital is formed and managed, introducing new instruments and requiring a coherent ecosystem for their effctive use. This creates a scientifi and practical problem of overcoming the fragmentation of contemporary digital instruments for private wealth management. Addressing this problem defies the purpose of the study as substantiating the theoretical foundations for the development of digital private wealth management. The research objective is achieved through the use of systems analysis, conceptual modeling, and the DomainDriven Design (DDD) methodology. The conceptualization of the domain is implemented through the development of a holistic model of digital private wealth management that synthesizes behavioral, values-based, and distributedledger-technology-based instruments. The behavioral model replaces static questionnaires with a dynamic behavioral profie that can identify and mitigate an investor’s cognitive biases in real time. The values-based model translates the client’s subjective non-fiancial goals into quantifible fiters for multi-criteria portfolio optimization. The tokenization model describes the process of transforming illiquid real assets into fractional digital security tokens using a blockchain platform and smart contracts. The integration model, implemented through an artifiial intelligence-driven simulation engine, links the private investor’s long-term life goals with the current state of the portfolio and provides automated responses to triggers, such as life events and market volatility. The scientifi novelty of the study lies in synthesizing these four models into a coherent domain ontology for organizing private wealth management. This ontology captures the consolidation of digital instruments required to implement hyperpersonalized wealth management, while simultaneously taking into account the private investor’s behavioral and cognitive preferences, personal values, and life plans.
Theoretical foundations for the development of digital financial instruments in private wealth management
Keywords: цифрові фінансові інструменти; управління приватним капіталом; токенізація активів; поведінкові фінанси; організація управління; digital fiancial instruments; private wealth management; asset tokenization; behavioral fiance; governance design